Annotation and cluster analysis of long noncoding RNA linked to male sex and estrogen in cancers - Liu, Shouping (NPJ Precis Oncol, 2020)
The sex difference in cancer occurrence is a consistent finding in cancer epidemiology. Several solid tumors, including lung cancer, colorectal cancer, hepatic carcinoma, and renal carcinoma, are generally more common in males. Although sexual dimorphism is attributed to hormonal or behavioral differences, evidence for the function of lncRNA is lacking in sex-specific cancers. We show here that LINC00263 is one of the most dysregulated lncRNAs in lung adenocarcinomas and is upregulated in lung adenocarcinoma, colorectal cancer, and renal carcinoma, especially in male patients compared to females. LINC00263 functions as an oncogene by promoting translocation of p65 into the nucleus to activate the NF-κB-signaling pathway through interaction with IKKα in the cytoplasm. The expression of LINC00263 is strongly correlated with ESR1, and it is decreased after treatment with estrogen. Ligand-activated ER could inhibit the function of LINC00263 by inhibiting NF-κB from cytoplasmic translocation into the nucleus. The inhibitory effect of estrogen on LINC00263 indicates its differential expression in male and female patients. Our findings indicate that LINC00263 is linked to male sex and estrogen as an oncogene, and these findings might help in the exploration of the mechanisms of differential gene regulation in sex-specific cancers.